Bioinspired hydrophobic pseudo-hydrogel for programmable shape-morphing - Zhigang Wang; Haotian Hu; Zefan Chai; Yuhang Hu; Siyuan Wang; Cheng Zhang; Chunjie Yan; Jun Wang; Wesley Coll; Tony Jun Huang; Xianchen Xu; Heng Deng (Nature Communications)
Abstract Inspired by counterintuitive water “swelling” ability of the hydrophobic moss of the genus Sphagnum (Peat moss), we prepared a hydrophobic pseudo-hydrogel (HPH), composed of a pure hydrophobic silicone elastomer with a tailored porous structure. In contrast to conventional hydrogels, HPH achieves absorption-induced volume expansion through surface tension induced elastocapillarity, presenting an unexpected absorption-induced volume expansion capability in hydrophobic matrices. We adopt a theoretical framework elucidating the interplay of surface tension induced elastocapillarity, providing insights into the absorption-induced volume expansion behavior. By systematically programming the pore structure, we demonstrate tunable, anisotropic, and programmable absorption-induced expansion. This leads to dedicated self-shaping transformations. Incorporating magnetic particles, we engineer HPH-based soft robots capable of swimming, rolling, and walking. This study demonstrates a unusual approach to achieve water-responsive behavior in hydrophobic materials, expanding the possibilities for programmable shape-morphing in soft materials and soft robotic applications.